Challenges of Digital Building Data Usage with a Focus on the Digital Documentation of Heritage Buildings—Results from an Online Survey - Ahmed Khalil; Spyridon Stravoravdis (Heritage, 2022)
The AEC industries as well as the heritage sector are facing a number of issues that relate to the management of building digital data. Two of the most prominent ones are the interoperability of data and data longevity. In order to better understand the extent of these issues for the general AEC industry and heritage buildings sectors, an online survey was designed to help quantify them and reveal the opinions of professionals and academics in the field. The online survey highlighted a clear latency in BIM adoption in the heritage sector as only 51% of the heritage participants use BIM in their projects compared to 63% of AEC participants. The reasons for this were further explored in the participants’ comments, as most of the reasons revolved around the issues of BIM data interoperability and longevity, considering the complex and interdisciplinary nature of heritage projects. The survey responses highlighted that data longevity is a crucial challenge for the heritage sector in particular as the need for future re-accessibility of digital data is clear in the results, showing that more than 82% of the heritage participants need to re-access their data in the future. The results also showed the prevalence of BIM interoperability issues and highlighted that the heritage sector is more prone to interoperability issues compared to the general AEC industry as 67% of heritage BIM participants and 50% of AEC BIM participant have faced some issues of BIM interoperability. In total, 72% of the standardised BIM participants agreed that standardised BIM formats could be a promising solution to mitigate the interoperability challenges, while only 57% thought that standardised BIM formats are reliable in their current status. Moreover, the online survey explored the variation in the needs of different disciplinary groups including rates of BIM adoption, use of standardised BIM formats, and needs for access to different heritage buildings data categories. Participants also presented their views on what would be an ideal medium for long-term storage of heritage buildings digital documentation data for future access, with some views being sceptical concerning BIM in its current status. This paper presents the findings of this extensive online survey.